1997
DOI: 10.1159/000217430
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of C4b-Binding Protein Isoforms during the Acute Phase Response Caused by Orthopedic Surgery

Abstract: Orthopedic surgery is described as an event with a high risk of thromboembolic diseases. This is probably a consequence of a synergistic combination of different risk factors in the patients subjected to this type of surgery, including age, immobilization, anesthesia and different hypercoagulable states. After surgery patients develop an acute-phase response that leads to changes in several plasma proteins. One of these proteins is the complement regulator C4b-binding protein (C4BP). We have recently shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…However, a similar requirement for prolonged stimulation with cytokines to increase CD55 expression has been reported for human lung carcinoma cell lines [12]. Our findings are also in agreement with the effects of the AP response in patients: for example, no increase in the serum levels of C4bp are seen in the first 24 h, but are instead observed over a 3±9-day period post-surgery [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, a similar requirement for prolonged stimulation with cytokines to increase CD55 expression has been reported for human lung carcinoma cell lines [12]. Our findings are also in agreement with the effects of the AP response in patients: for example, no increase in the serum levels of C4bp are seen in the first 24 h, but are instead observed over a 3±9-day period post-surgery [26].…”
Section: Discussionsupporting
confidence: 91%
“…Because we were unable to obtain primary hepatocytes, we chose a well‐characterized hepatoma cell line, Hep3B, and examined the effects of cytokines implicated in the AP response on expression of C regulators by the cells. A second hepatoma cell line, HepG2, was also examined and gave broadly similar results, but we chose to present results from Hep3B because we have previously found in studies of effects of AP response cytokines on expression of the fluid‐phase C regulatory protein, C4bp, that the response to AP cytokines in the latter cell more closely mirrors changes observed in vivo [16,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this observation could be that the endotoxin dose was too low or the duration of the stimulus was too short to elicit an increase in C4BP, or that C4BP exhibits a delayed response. The latter is supported by the observation that increases in C4BP after orthopedic surgery do not become manifest until 48 h after surgery [14]. Another explanation for our observations could be that the APR activates the classical complement pathway modulated by C4BP leading to C4BP consumption and a subsequent transient decrease in C4BP levels [15].…”
supporting
confidence: 71%
“…This suggests that protein S and C4BP β + are not actively regulated during the APR. The transient decrease of total C4BP and C4BP β + and the subsequent lack of increase of their concentration above baseline was at first sight unexpected as it has been reported that the APR in patients increases the level of total C4BP, largely because of an increase in C4BP β ‐ [10,14]. Possible explanations for this observation could be that the endotoxin dose was too low or the duration of the stimulus was too short to elicit an increase in C4BP, or that C4BP exhibits a delayed response.…”
mentioning
confidence: 99%
“…Other studies, however, provide evidence for stable free PS levels during inflammation, showing only a rise in C4BP ␣-chain levels, but not in ␤-chain levels. 21,25 The observed discrepancy between the various studies may be explained by a differential regulation of C4BP ␣-and ␤-chains in different subpopulations of patients during the APR. 26 The IL-6 signaling pathway is well-defined.…”
mentioning
confidence: 99%